2022
DOI: 10.1007/s11665-022-07438-4
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Quench and Partitioned Steels Against Hydrogen Embrittlement

Abstract: Multiphase ultra-high strength steels (UHSS) containing retained austenite (RA) appear to be among the most interesting steels for the automotive industry. Developments in the last decades have allowed obtaining a very good combination of mechanical strength and ductility. Quenching and partitioning (Q&P) steels have been proposed as third-generation UHSS, reaching ultimate tensile strength up to 1300 MPa along with excellent fracture elongations of more than 15%. However, the use of Q&P steels is main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…[8,9] Therefore, the qualification of structural materials with respect to their resistivity against hydrogen embrittlement mainly relies on experimental testing and standards. [10,11] Autoclave systems for testing and qualifying steels that are used in high-pressure applications of gaseous hydrogen are very common. [6,[12][13][14][15] Two different setups are widely used: 1) closed autoclaves that do not allow for any manipulation of the samples during testing, and 2) autoclaves with protruding sample holders for quasi-static testing or fatigue testing under high-pressure hydrogen atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] Therefore, the qualification of structural materials with respect to their resistivity against hydrogen embrittlement mainly relies on experimental testing and standards. [10,11] Autoclave systems for testing and qualifying steels that are used in high-pressure applications of gaseous hydrogen are very common. [6,[12][13][14][15] Two different setups are widely used: 1) closed autoclaves that do not allow for any manipulation of the samples during testing, and 2) autoclaves with protruding sample holders for quasi-static testing or fatigue testing under high-pressure hydrogen atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been found that various microstructures show quite different susceptibilities to HE. For QP steels, martensite, as a hard phase, is considered to be most sensitive to HE, while ferrite, as a soft phase, is considered to be less susceptible to HE [15]. However, as for RA, how it influences the HE is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Quenching and partitioning (Q&P) steels as a new class of advanced high-strength steels emerged in the early 2000s and has opened new avenues for producing ultra-high strength and formable steel grades [8]. The promising properties of Q&P steels demonstrated in the laboratory have led to extensive research efforts to understand their microstructure and properties [9]- [11]. However, industrial-scale adoption of Q&P steels has been relatively slow, owing to several factors.…”
Section: Introductionmentioning
confidence: 99%